Development And Characterization Of Coir Fibre Reinforced Composite Brake Friction Materials - Maleque, Md. Abdul; A., Atiqah (KFUPM, Saudi Arabia, 2013)
This paper presents the development and characterization of new natural fibre reinforced composite brake friction materials with a view to replace the asbestos fibre material whose dust is carcinogenic and has a harmful effect to the human being.